2018
DOI: 10.1111/cch.12623
|View full text |Cite
|
Sign up to set email alerts
|

Displaced Rohingya children at high risk for mental health problems: Findings from refugee camps within Bangladesh

Abstract: It is known that children escaping political violence are likely to be vulnerable. This study provides early evidence concerning recently displaced children in refugee camps within Bangladesh.Large proportions of children had emotional symptoms and peer problems. The most vulnerable were those without parents.As well as urgent needs for shelter, food and preventive healthcare, children require immediate psychosocial support in emergency situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Five studies, four of which included large samples (i.e. sample size ranging between 549 and 1,000), found no association between gender and mental health (Jensen, Skårdalsmo, & Fjermestad, 2014; Karam et al, 2019; Khamis, 2019; Khan et al, 2019; Mels, Derluyn, Broekaert, & Rosseel, 2010), albeit Mels et al (2010) found that girls are more likely to report internalising symptoms when experiencing high levels of daily stressors in post‐resettlement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies, four of which included large samples (i.e. sample size ranging between 549 and 1,000), found no association between gender and mental health (Jensen, Skårdalsmo, & Fjermestad, 2014; Karam et al, 2019; Khamis, 2019; Khan et al, 2019; Mels, Derluyn, Broekaert, & Rosseel, 2010), albeit Mels et al (2010) found that girls are more likely to report internalising symptoms when experiencing high levels of daily stressors in post‐resettlement.…”
Section: Resultsmentioning
confidence: 99%
“…In a study of refugees in Turkey children's psychopathology was linked with paternal education and paternal unemployment status (Sapmaz et al, 2017). No association was found between parental education and mental health of Rohingya children in Myanmar (Khan et al, 2019 & Montgomery, 2017;McGregor et al, 2016;Sim, Fazel, et al, 2018). For example, while fathers may report the value of positive parent-child interaction, there may find it difficult to control their anger and irritability prompted by the uninterrupted flow of daily stressors (Van Ee et al, 2013;Sim, Fazel, et al, 2018).…”
Section: Familial Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional study conducted among existing Rohingya refugees in Bangladesh before the 2017 exodus showed that 36% suffered from post-traumatic stress disorder (PTSD) and 89% suffered from depression [16]. Unsurprisingly, high rates of mental health problems were also common among children, with 52% of Rohingya children in Bangladesh having results in the abnormal range for emotional symptoms on the Strengths and Difficulties Questionnaire (SDQ), and 25% with results in the abnormal range for peer problems [31]. Rohingya refugees in Malaysia have similar high rates of comorbid mental health disorders, including 32% with PTSD, 9% with generalised anxiety disorders, and 12% with major depressive disorder [32].…”
Section: Discussionmentioning
confidence: 99%
“…The results point to an increasing concern about migrant children's well‐being in the last few years in academic research, with many recent papers published about this topic (Betawi, 2019 ; Burgos et al, 2019 ; Foka et al, 2020 ; Gatt et al, 2020 ; Khan et al, 2019 ; King & Said, 2019 ; Kneer et al, 2019 ; Metzler et al, 2019 ; Roupetz et al, 2020 ; Samara et al, 2020 ). This interest seems to be larger for the specific population of involuntary migrant children (refugees and asylum seekers) and not for other voluntary migrants.…”
Section: Discussionmentioning
confidence: 82%